A mulher em Rio Claro - SP: uma contribuição geográfica no estudo de gênero - Melo, Maria Alice de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Intersectionality brings great contributions to geographic production by favoring a systemic study of identity and social categories. Having the human being as the main transforming agent and creator of the geographical space, it is inherent to seek to understand the relations that govern it. This paper aims to contribute to the gender debate by electing women as investigative agents. The methodology of Relief Maps proposed by the geographer Rodó-de-Zarate (2013), fuses the spatial category with the identity characteristics of individuals, favoring the analysis of space in its human content. Besides the production of the graphic map, this analysis allows the reflection on the urban space characterizing the individuals in their experience in the concreteness of the places of the city. Focusing on the contribution of a geography that recognizes the gender disparities in its historical scientific production, the geographic and intersectional configuration of the experience of women in the city of Rio Claro - SP is presented

A interseccionalidade traz grandes contribuições para a produção geográfica ao favorecer um estudo sistêmico de categorias identitária e sociais. Tendo o ser humano como o principal agente transformador e criador do espaço geográfico, é inerente buscar compreender as relações que o regem. Este trabalho visa contribuir com o debate de gênero elegendo a mulher como agente investigativo. A metodologia dos Mapas de Relevo proposto pela geógrafa Rodó-de-Zarate (2013), funde a categoria espacial com as características identitárias dos indivíduos, favorecendo a análise do espaço em seu teor humano. Além da produção do mapa gráfico, esta análise permite a reflexão sobre o espaço urbano caracterizando os indivíduos em suas experiência na concretude dos lugares da cidade. Com foco na contribuição por uma geografia que reconheça as disparidades de gênero na sua histórica produção científica, apresenta-se a configuração geográfica e interseccional da experiência das mulheres no município de Rio Claro - SP
Keywords: Mulheres; Geografia; Identidade; Geografia humana; Espaços públicos; Geografia urbana; Cultura; Feminismo; Rio Claro (SP)